2021
DOI: 10.3389/fphy.2021.675509
|View full text |Cite
|
Sign up to set email alerts
|

Dipole-Fed Rectangular Dielectric Resonator Antennas for Magnetic Resonance Imaging at 7 T: The Impact of Quasi-Transverse Electric Modes on Transmit Field Distribution

Abstract: Shortened dipole antennas based on rectangular dielectric blocks play an important role in ultrahigh field magnetic resonance imaging (UHF-MRI) radio frequency (RF) coil design. However, the generally assumed direct contact with the subject is difficult to maintain in typical in vivo settings. We have previously observed that certain dielectrically shortened dipole antennas can produce a substantially altered transmit field distribution with a very low transmit efficiency when the block and the sample are phys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 28 publications
0
13
0
Order By: Relevance
“…In particular, a case in which both the diameter and length increased while maintaining a D/L-ratio of 0.7 in the 7.0 T results, the normalization factors provided almost constant RF transmission efficiency without linear increase or decrease. This result shows that the B 1 + -field transmission efficiency in UHF MRI was determined not by the structure of the RF coil, but by the dielectric properties and geometry of loaded object [68,69].…”
Section: Resultsmentioning
confidence: 84%
“…In particular, a case in which both the diameter and length increased while maintaining a D/L-ratio of 0.7 in the 7.0 T results, the normalization factors provided almost constant RF transmission efficiency without linear increase or decrease. This result shows that the B 1 + -field transmission efficiency in UHF MRI was determined not by the structure of the RF coil, but by the dielectric properties and geometry of loaded object [68,69].…”
Section: Resultsmentioning
confidence: 84%
“…Those reports focused on the dipole antenna design, and the influence of dielectric modes on the transmit field distribution was not emphasized. However, a recent study of ours showed that dipole antennas, which are in contact with a dielectric block, act as dipole-fed dielectric resonator antennas [24]. They can couple, just like loops, to different types of TE modes formed within rectangular blocks (especially if the cutoff frequency for a given dielectric mode is below the Larmor frequency), and such modes have a major impact on the B 1 + distribution.…”
Section: Introductionmentioning
confidence: 90%
“…prostate [19,25], it is unknown whether the same is true in the context of human brain MRI at 7 T. The human head is a significantly smaller anatomical structure, and its size could be a factor limiting the benefit from the "far-field effect" at 300 MHz which is much more pronounced for body MRI [19]. Moreover, the interaction between a given dielectric mode and a sample depends on the sample's geometry [24]. This means that any findings reported for a large rectangular phantom, mimicking human body, cannot be directly applied in the context of the human brain, which is closer to a spherical geometry.…”
Section: Introductionmentioning
confidence: 99%
“…Several other groups have also considered various aspects of DR operation at high fields. Wenz et al [ 94 ] have investigated the different modes of a DR that can be excited using a dipole feed, and why certain configurations preserve (and others do not) the transmit field distribution and efficiency if there is a gap between resonator and subject [ 94 ]. The group in Utrecht have used HPMs to improve the B 1 + penetration and reduce the SAR of various forms of dipole antenna [ 95 , 96 ].…”
Section: New Materials In Designing Transmit and Receive Resonatorsmentioning
confidence: 99%